Seismic volcanostratigraphy of the NE Greenland continental margin - Geissler, Wolfram H.; Gaina, Carmen; Hopper, John R.; Funck, Thomas; Blischke, Anett; Árting, Uni Egholm; Á Horni, Jim; Péron-Pinvidic, Gwenn; Abdelmalak, Mohamed Mansour (Geological Society, London, Special Publications, 2018)
The Early Eocene continental break-up between the NE Greenland and the mid-Norwegian–SW Barents Sea margins was associated with voluminous magmatism and led to the emplacement of massive volcanic complexes including wedges of seawards-dipping reflections (SDR). We study the distribution of these break-up-related volcanic rocks along the NE Greenland margin by revisiting existing seismic reflection data and comparing our observations to better-studied segments of the conjugate margin. Seismic facies types match between the conjugate margins and show strong lateral variations. Seaward-dipping wedges are mapped offshore East Greenland, the conjugate to the Vøring continental margin. The geophysical signature of the SDRs becomes less visible towards the north, as it does along the conjugate Lofoten–Vesterålen margin. We suggest that the Traill Ø volcanic ridge is a result of plume–ridge interactions formed between approximately 54 and 47 Ma. North of the East Greenland Ridge, strong basement reflections conjugate to the Vestbakken Volcanic Province are interpreted as lava flows or ‘spurious’ SDRs. We discuss our findings in conjunction with results from seismic wide-angle experiments, gravity and magnetic data. We focus on the spatial and temporal relationships of the break-up volcanic rocks, and their structural setting in a late rift and initial oceanic drift stage.